The Effect of Prolonged Sitting on Thoracic Spine Mobility among College Students - Poovarasan, Murugaiyan; J., Saravankumar (INTI International University, 2023)
Background and aims: Sitting over a prolonged period not only creates physiological health problem and cardiovascular diseases, but also increases the risk of musculoskeletal disorders. The goal of this study is to determine whether there is a link between thoracic spine mobility and prolonged sitting, and the objectives are, to assess whether there is a connection between the length of time spent sitting and the mobility of the thoracic spine and examine the effect of extended sitting on the mobility of the thoracic spine. Methodology: The inclusion and exclusion criteria were checked on patients who were willing to participate in the study, they will provide an overview of the study before measuring thoracic mobility using methods such as the sitting rotation test (bar in front), in order to limit movement in participants lower extremities during thoracic rotation, a small ball was placed between their knees and a PVC bar with a tape marker at the halfway also used, which helps to fix the upper extremity. Using revised Oswestry to measure thoracic disability levels, the values were evaluated. Results: The statistical analysis showed that those who spend more time in sitting had limited thoracic rotation range of motion. Also, the questionnaire of thoracic pain showed pain and high disability index who spend more time in sitting and travelling. Conclusion: In people who spend more than 7 to 8 hours sitting, the study’s findings showed that their thoracic spine mobility was decreased. According to the questionnaire, people who spend a lot of time sitting and travelling during the course of a day as well as those who experience discomfort or restriction when performing ADLs had a high disability index for thoracic spine pain.